2013
DOI: 10.1371/journal.pone.0062955
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor Discovery of Full-Length New Delhi Metallo-β-Lactamase-1 (NDM-1)

Abstract: New Delhi metallo-β-lactmase-1 (NDM-1) has recently attracted extensive attention for its biological activities to catalyze the hydrolysis of almost all of β-lactam antibiotics. To study the catalytic property of NDM-1, the steady-kinetic parameters of NDM-1 toward several kinds of β-lactam antibiotics have been detected. It could effectively hydrolyze most β-lactams (k cat/K m ratios between 0.03 to 1.28 µmol−1.s−1), except aztreonam. We also found that thiophene-carboxylic acid derivatives could inhibit NDM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
(36 reference statements)
1
30
0
Order By: Relevance
“…Proteins were expressed in E. coli BL21(DE3) cells and purified by affinity chromatography as described previously (12). The purified protein was dialyzed at 4°C against 50 mM HEPES buffer (pH 7.0) supplemented with 250 mM NaCl and 100 M ZnCl 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were expressed in E. coli BL21(DE3) cells and purified by affinity chromatography as described previously (12). The purified protein was dialyzed at 4°C against 50 mM HEPES buffer (pH 7.0) supplemented with 250 mM NaCl and 100 M ZnCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…All the experiments were carried out in 50 mM HEPES buffer (pH 7.0) containing 250 mM NaCl and 100 M ZnCl 2 at 30°C as described previously (12). Bovine serum albumin (BSA; 20 g/ml) was added in the dilution buffer to prevent denaturation of NDM-1 and Trp93Ala mutant proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of VIM‐2 was induced by 0.2 mM IPTG when the absorbance at 600 nm reached 1.0–1.5. The cells were disrupted by sonication, and the supernatant of the cell lysate was further purified by nickel‐chelating affinity method as previous described 43…”
Section: Methodsmentioning
confidence: 99%
“…Using the two-stage protein flexible docking protocol mentioned in the methodology section [43], Shen et al established an interaction model for NDM-1 and the thiophene-carboxylic acid inhibitor. The results revealed that sulfur atoms of ligand might interfere with the water bridge and zinc ions in the active site of NDM-1, which provide useful clues for the rational design of effective NDM-1 inhibitors [78].…”
Section: Cases Of Hit Discoverymentioning
confidence: 99%